'Not just a miscarriage' : the social and cultural perspectives of miscarriage among urban Malay women - Nurulwahida binti Saad (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, 2018)
This study explores the social and cultural perspectives of miscarriage among urban Malay women. The objectives of the study included examining the meanings, beliefs, rituals, health seeking behaviour and the role of health care systems in dealing with miscarriage. The study adopted a qualitative approach that included in-depth interviews using a multi-sited ethnography and participant observation. The fieldwork was conducted over a period of 13 months from April 2014 until May 2015. 30 primary informants were selected purposively and were of Malay ethnicity, working and residing in the Klang Valley and had at least one experience of miscarriage. Two focus group discussions (FGDs) were also conducted with women with no experience of miscarriage and in-depth interviews conducted with three medical doctors. The interviews were audio recorded, transcribed and translated into English and the data analysed using thematic analysis. Two major themes emerged: (1) the sacred side of miscarriage and; (2) miscarriage as an interpersonal event. The first theme explores the sanctifying behaviours, attitudes, and beliefs associated with miscarriage rooted in the informants meanings of pregnancy and the Adāt and Islamic characteristics of Malay culture. Findings revealed that Malay women attributed miscarriages to a number of factors including cultural food beliefs, God's will, the evil eye and jinn, work and lifestyle factors such as physical activity, stress and emotional upset. The sacredness of miscarriage was also evident in the food prohibitions and cleanliness and 'dirt' avoidance rituals practiced in the post-miscarriage confinement practices. The second theme explores miscarriage as an interpersonal event where the people the informants interacted with shaped and impacted how she experienced her miscarriage. Good doctor-patient relationships, supportive husbands and comforting friends and family all helped the informants cope with their personal reactions and emotional responses to their miscarriage. These positive social support systems helped console, remind and encourage the informants to develop self coping strategies by connecting with their Islamic andspiritual beliefs and practices. Incidences of negative or insensitive reactions from others were found to be due to lack of personal experience, knowledge and understanding of miscarriage which in turn shaped miscarriage as a social stigma. The study concludes that miscarriage is more than just a physiological event but is also a lived experience governed by social, cultural, religious and medicalframeworks. By understanding miscarriage within the socio-cultural Malay context, we can enhance healthcare systems to fill the gap between culture and medicine by substantiating Malay cultural guidelines as points of reference to provide culturally relevant policies for comprehensive and holistic medical management of miscarriage. This includes creating awareness and organising campaigns for the importance of antenatal education, and an increased sensitivity towards women who experience miscarriage. In addition, suggestion of a collaboration between traditional healers, healthcare providers and counsellors to provide post-miscarriage physical and psychological care for women who have miscarried, may promote healthy healing and coping for women after miscarriage.